Identification of core cuprotosis-correlated biomarkers in abdominal aortic aneurysm immune microenvironment based on bioinformatics - Hu, Jiateng; Xue, Song; Xu, Zhijue; Wu, Zhaoyu; Xu, Xintong; Wang, Xin; Liu, Guang; Lu, Xinwu; Li, Bo; Liu, Xiaobing (Frontiers in Immunology, 2023)
Background The occurrence of abdominal aortic aneurysms (AAAs) is related to the disorder of immune microenvironment. Cuprotosis was reported to influence the immune microenvironment. The objective of this study is to identify cuprotosis-related genes involved in the pathogenesis and progression of AAA. Methods Differentially expressed lncRNAs (DElncRNAs) and mRNAs (DEmRNAs) in mouse were identified following AAA through high-throughput RNA sequencing. The enrichment analyses of pathway were selected through Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG). The validation of cuprotosis-related genes was conducted through immunofluorescence and western blot analyses. Results Totally, 27616 lncRNAs and 2189 mRNAs were observed to be differentially expressed (|Fold Change| ≥ 2 and q< 0.05) after AAA, including 10424 up-regulated and 17192 down-regulated lncRNAs, 1904 up-regulated and 285 down-regulated mRNAs. Gene ontology and KEGG pathway analysis showed that the DElncRNAs and DEmRNAs were implicated in many different biological processes and pathways. Furthermore, Cuprotosis-related genes (NLRP3, FDX1) were upregulated in the AAA samples compared with the normal one. Conclusion Cuprotosis-related genes (NLRP3,FDX1) involved in AAA immune environment might be critical for providing new insight into identification of potential targets for AAA therapy.